Racial, Ethnic, and Color-Based Discrimination and Pre-Pregnancy Risk Factors for Preeclampsia Among Nulliparous Patients - Alexa I.K. Campbell; Maria J. Small; Sarahn M. Wheeler; Jerome J. Federspiel (Health Equity)
Introduction: Obesity and chronic hypertension are well-known risk factors for maternal morbidity and mortality. Evidence suggests racism contributes to the development of these chronic conditions. Methods: We conducted a secondary analysis of the Nulliparous Pregnancy Outcomes: monitoring mothers-to-be (nuMoM2b) cohort, which recruited nulliparous pregnant participants in the United States in 2010–2013. Using logistic regression, we assessed the relationship between experiences of racial, ethnic, and color-based (REC) discrimination (categorized as high, low, or no REC discrimination) and prevalence of a composite outcome of obesity and/or chronic hypertension. Results: Among 8,554 participants, the composite outcome was unequally distributed by race and ethnicity (p < 0.001), present in 19.9% of non-Hispanic White, 23.1% of Hispanic, and 39.0% of non-Hispanic Black participants. Self-reported REC discrimination was similarly unequally distributed (p < 0.001), with high REC discrimination reported by 17.5% of non-Hispanic Black, 10.6% of Hispanic, and 2.1% of and non-Hispanic White participants. In multivariable analyses, high self-reported REC discrimination was associated with a 1.75 adjusted odds ratio (95% confidence interval: 1.43–2.14) of the composite outcome compared with those reporting no REC discrimination. When stratified by race and ethnicity, the odds ratios for the composite outcome among those reporting high REC discrimination were only statistically significant among the Hispanic subgroup. Conclusion: We observed a positive, dose-dependent association between self-reported REC discrimination and our outcome of obesity and/or chronic hypertension. By demonstrating this relationship in an obstetric cohort, we aim to highlight the role of racism over the life course in contributing to chronic health conditions and associated maternal outcomes.